2012
DOI: 10.1261/rna.035048.112
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of Trypanosoma brucei editosome proteins KREPB4 and KREPB5 reveals domains critical for function

Abstract: The transcriptome of kinetoplastid mitochondria undergoes extensive RNA editing that inserts and deletes uridine residues (U's) to produce mature mRNAs. The editosome is a multiprotein complex that provides endonuclease, TUTase, exonuclease, and ligase activities required for RNA editing. The editosome's KREPB4 and KREPB5 proteins are essential for editosome integrity and parasite viability and contain semi-conserved motifs corresponding to zinc finger, RNase III, and PUF domains, but to date no functional ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(70 citation statements)
references
References 47 publications
11
59
0
Order By: Relevance
“…In contrast, the subcomplexes in KREN1-TAP eluates primarily contained insertion subcomplexes, as seen by the greater abundance of KREPA1 compared with KREPA2 and KREL1. These observations are consistent with previous studies that indicated that KREPB5 is most stably associated with the deletion subcomplex (30) and the endonucleases primarily associate with the insertion subcomplex (23,29). The compositions of the complexes and subcomplexes in the two different purifications provided a rationale for subsequent analysis of both KREN1-TAP and KREPB5-TAP eluates.…”
supporting
confidence: 90%
See 4 more Smart Citations
“…In contrast, the subcomplexes in KREN1-TAP eluates primarily contained insertion subcomplexes, as seen by the greater abundance of KREPA1 compared with KREPA2 and KREL1. These observations are consistent with previous studies that indicated that KREPB5 is most stably associated with the deletion subcomplex (30) and the endonucleases primarily associate with the insertion subcomplex (23,29). The compositions of the complexes and subcomplexes in the two different purifications provided a rationale for subsequent analysis of both KREN1-TAP and KREPB5-TAP eluates.…”
supporting
confidence: 90%
“…The proximity of KREPB4 to all endonucleases is intriguing given that KREPB4 is one of two editosome proteins, in addition to KREPB5, previously shown to contain a degenerate noncatalytic RNase III domain (30,31). We detected cross-links, and therefore proximity, between the RNase III domains of each of the endonucleases, and the region flanked by the U1-like zinc finger and RNase III domain, and the C-terminal domain in KREPB4 (Fig.…”
mentioning
confidence: 75%
See 3 more Smart Citations